2021
DOI: 10.1097/ncc.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Its Associated Factors in Prostate Cancer Patients Who Receive Androgen Deprivation Therapy

Abstract: Background Presently, few studies have examined the impact of positive thinking on the HRQoL of prostate cancer patients who receive androgen deprivation therapy (ADT). Objectives We explored the factors that affect health-related quality of life (HRQoL), particularly positive thinking, of prostate cancer patients who receive ADT. Methods A cross-sectional design was used. A total of 132 prostate cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 39 publications
1
24
1
Order By: Relevance
“…Research on patients with prostate cancer has shown that patients who think positively experience better quality of life. 15 These findings highlight the importance of understanding positive thinking and associated factors in patients with prostate cancer. Few studies, however, have explored the positive thinking of prostate cancer patients and related factors, especially social support, treatment satisfaction, and self-efficacy.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…Research on patients with prostate cancer has shown that patients who think positively experience better quality of life. 15 These findings highlight the importance of understanding positive thinking and associated factors in patients with prostate cancer. Few studies, however, have explored the positive thinking of prostate cancer patients and related factors, especially social support, treatment satisfaction, and self-efficacy.…”
mentioning
confidence: 93%
“…A study of cancer patients and their caregivers by Hamidou et al 21 showed that patients who are positive thinkers have better mental health-related quality of life than do those who are not. In addition, a study of patients with prostate cancer found that patients who think positively experience better functional well-being, emotional well-being, social/family well-being, and prostate cancer–specific quality of life 15 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease may be gradually accepted through these means of coping. Recent studies have also shown that positive thinking and a positive attitude towards life are important factors in the quality of life of (Chien et al, 2021) patients with PC or prostate cancer (Branney et al, 2014;Jantunen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%